Labour market reform and the sustainability of exchange rate pegs - Olli Castrén; Tuomas Takalo; Geoffrey Wood (European Central Bank (ECB), 2004)
It is commonly thought that an open economy can accommodate output shocks through either exchange rate or real sector adjustments. We formalise this notion by incorporating labour market rigidities into an “escape clause” model of currency crises. We show that the absence of structural reform makes a currency peg more fragile and undermines the credibility of the monetary authority in a dynamic setting. The fragility is captured by a devaluation premium in expectations that increases the average inflation rate when the currency peg is more vulnerable to “busts” than “booms”. This interaction between macroeconomic and microeconomic rigidities suggests that a policy reform can only be consistent if it renders either exchange rates or labour markets flexible.
Keywords: E42; F33; D84; 330; Exchange rate policy; labour market flexibility; structural reform